Effectiveness of the laparoscopic appendectomy on second half of the pregnancy - Aziret, Mehmet; Akdeniz, Yesim; Karaman, Kerem; Altintoprak, Fatih; Karacaer, Cengiz; Mantoglu, Baris; Alper Yildiz, Yasin; Ercan, Metin (Annals of Medical Research, 2021)
Aim: Although the debate regarding fetal loss and preterm delivery continues, the use of laparoscopic appendectomy (LA) to treat pregnant women has gained legitimacy owing to the advantages it brings, such as less uterine manipulation, less postoperative pain, and an early return to normal daily activity. This present study aims to compare the impact of LA on women in early and late gestation periods with regard to surgical outcomes.Material and Methods: After scanning the files of 4,295 cases, 29 patients who underwent LA for acute appendicitis during pregnancy were enrolled in the study and were assessed retrospectively. The patients were divided into two groups: women with a gestation period less than 20 weeks (group 1; n=19) and those over 20 weeks (group 2; n=10). Data from these two groups, including patient perioperative characteristics and morbidity, were compared.Results: The results showed no statistical difference between the two groups. No statistically significant difference was detected in terms of mean age, body mass index, length of hospital stay, operation time or median ASA score (p > 0.05). Moreover, mean INR (International normalized ratio), hemoglobin, hematocrit, white blood cell count, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, red cell distribution width, platelet distribution width and histopathological examination of the appendicitis revealed no statistical difference between the two groups (p > 0.05). Most importantly, comparison of surgical site infection (6.8%), intra-peritoneal collection (3.4%), fetal distress and preterm delivery rate (6.8%), and abortus imminens (3.4%) also showed no significant difference (P > 0.05). In this study, no fetal loss was recorded.Conclusion: The results of present study suggest that LA for acute appendicitis in pregnant women can be performed safely during the second half of pregnancy.